Educar e educar-se na diversidade: uma relação com as danças das culturas populares no Brasil e em Moçambique - Foganholi, Cláudia (Universidade Federal de São Carlos, 2015)
The expression educate and educate yourself, committed to a liberating education, is based on the understanding that education is not realized in action to educate someone, but to educate yourself in a respectful sharing process of knowledge. Dance experienced in the context of Popular Culture is, in this thesis, the driver element of chance to educate and educate themselves in communion . In this sense , this study aims to understand how people involved in the social practice of popular cultures dances educate and educate themselves in relation to the different ways of being in the world. For this purpose, sought to reveal the contributions of educative processes generated in this practice, in Brazil and Mozambique, for the construction of a pedagogical practice based in the affirmation of differences and valuing diversity. The construction of this thesis and praxis involved in interventions is based on the theoretical frameworks that are articulated around the studies of Human Motricity, the Dialogic Pedagogy and South Epistemologies. The relationship of these references brings up an ontological perspective based in the transcendence of the human being, in other words, in its ability to transform and change the world, his vocation to be more. The universe of transcendence or the vocation to be more are related, especially the possibilities of overcoming oppressive and dehumanizing realities, of objectification of human beings. The research field consists of two moments of insertion, one in Brazil and another in Mozambique, in which were offered the experience of dances of popular cultures to groups of children and adolescents, comprising the historical, social context and the educative processes inherent in such practice. The data presented comprise the registers in field diaries, whose analysis was performed from phenomenological inspiration. Launching in defense of the educational potential of manifestations of popular cultures, this thesis presents between the results obtained performing dances as favorable to the construction of intersubjectivity spaces and dialogical postures in the process of educate and educate themselves, in communion, in relation to diversity. Among the educative processes generated in the dances of popular cultures we can observe that indicate the different ways of being in the world as constituent parts of a community and an essential condition of its existence.
Keywords: Práticas sociais e processos educativos; Dança; Cultura popular; Pedagogia dialógica; Motricidade; Dance; Popular culture; Dialogic pedagogy; Human motricity; Educative processes; CIENCIAS HUMANAS::EDUCACAO